2018
DOI: 10.3906/sag-1802-126
|View full text |Cite
|
Sign up to set email alerts
|

The comparison between propofol and dexmedetomidine infusion on perioperative anxiety during regional anesthesia

Abstract: Background/aim: Regional anesthesia for surgery is associated with increased anxiety for patients. This study aimed to compare the effect of propofol and dexmedetomidine infusion on perioperative anxiety during regional anesthesia.Materials and methods: Eighty-four patients were randomly divided into two groups receiving either study drug infusion. Anxiety score, level of sedation using the Bispectral Index and Observer's Assessment of Alertness and Sedation, hemodynamic stability, and overall patient's feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Perhaps the difference in anxiety findings between the mentioned study and ours is due to differences in dose, method, and timing of drug administration [ 30 , 31 ]. In the study of Lim and colleagues on patients undergoing central neuroaxial blockade, the effect of the infusion of propofol and dexmedetomidine was compared; the researchers reported that dexmedetomidine caused a greater reduction in postoperative anxiety compared with propofol [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the difference in anxiety findings between the mentioned study and ours is due to differences in dose, method, and timing of drug administration [ 30 , 31 ]. In the study of Lim and colleagues on patients undergoing central neuroaxial blockade, the effect of the infusion of propofol and dexmedetomidine was compared; the researchers reported that dexmedetomidine caused a greater reduction in postoperative anxiety compared with propofol [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 A substantial body of clinical research indicates that dexmedetomidine can alleviate anxiety levels in perioperative patients. 7,8 Loh et al 9 found that dexmedetomidine can effectively reduce anxiety during magnetic resonance imaging examinations in adults. Chlan et al 10 found that dexmedetomidine effectively alleviated anxiety in intensive care unit patients.…”
Section: Editor's Perspectivementioning
confidence: 99%
“…Patients remain conscious during local anesthesia, which may increase perioperative anxiety 1 that exposes patients to greater surgical risk, 2 such as hemodynamic fluctuations, pain, and so forth. 3 Regional anesthesia‐assisted sedation has the advantages of reducing intraoperative bleeding, fast postoperative recovery, and so on, making it conducive to clinical application. 4 However, at present, commonly used clinical sedative drugs include propofol, midazolam, dexmedetomidine, and so on, each with limitations that restrict their utility.…”
Section: Introductionmentioning
confidence: 99%